2002
DOI: 10.1128/jvi.76.22.11561-11569.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Macaques with Formalin-Inactivated Respiratory Syncytial Virus (RSV) Induces Interleukin-13-Associated Hypersensitivity to Subsequent RSV Infection

Abstract: Respiratory syncytial virus (RSV) is a major cause of severe respiratory disease in infants and the elderly. RSV vaccine development has been hampered by results of clinical trials in the 1960s, when formalininactivated whole-RSV preparations adjuvated with alum (FI-RSV) were found to predispose infants for enhanced disease following subsequent natural RSV infection. We have reproduced this apparently immunopathological phenomenon in infant cynomolgus macaques and identified immunological and pathological corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 46 publications
5
99
2
Order By: Relevance
“…The prolonged duration of signs of lower respiratory tract disease in the infant baboon provides an excellent endpoint to assess the effects of antivirals and vaccines in reducing or preventing RSV-related illness. No other nonhuman primate model has been reported to demonstrate tachypnea or reduced oxygenation following infection with RSV (5,11,17,26,27,30).…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged duration of signs of lower respiratory tract disease in the infant baboon provides an excellent endpoint to assess the effects of antivirals and vaccines in reducing or preventing RSV-related illness. No other nonhuman primate model has been reported to demonstrate tachypnea or reduced oxygenation following infection with RSV (5,11,17,26,27,30).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was first observed in a human vaccine trial in the 1960s [4] and was later found to also occur in cattle immunized with formalin-or beta-propriolactone-inactivated bRSV [5,6]. Enhanced disease resulting from immunization with Fl-virus has an immunopathological basis and has now been modeled in hRSV-infected mice [2,[7][8][9] and monkeys [10] and in bRSV-infected cattle [1,[11][12][13]. In mice, immunization with inactivated virus evokes a Th-2 biased CD4 T cell response, which is associated with eosinophilia and clinical symptoms upon challenge [2].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of enhanced disease in FI vaccinated infants a�er subsequent naturally infection is not fully understood. However, the animal model suggests that it was due to strong T-cell priming which predominantly produces Th2 cytokines interleukin-4 (IL-4), IL-5, and IL-13 and induce eosinophilic response (Openshaw et al, 2001;De Swart et al, 2002). Such an unexpected effect of vaccination led to a more detailed study of the immune response to the respiratory syncytial viruses.…”
Section: Immune Responsementioning
confidence: 99%